CREATION OF OBJECT RECOGNITION AND TRACKING SYSTEM - KRYVENCHUK, Yurii; MARKO, Oleksandra (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In modern society, video recording systems have become widespread, allowing them to recognize objects, their absence, and changes in position. In the vast majority of intelligent systems for video monitoring and determining objects through their image, such objects as human faces, printed publications, and state registration numbers are taken into consideration. At the same time, the circumstances for accepting an image are quite strict, since there is a limit on illumination, background, location relative to the lens, and so on. All this significantly facilitates the joint work of a person with a computer, and creates the prerequisites for using all kinds of systems of artificial origin of the mind. The primary goal in the development of a method and software for the automatic design of a video surveillance system is the purpose of recognize an object whose image is transmitted through the camera. Since the image of any object depends on many moments of its direction about the video camera, illumination, characteristics of the recorder, static and dynamic characteristics of the object, it is rather difficult to arrange and present a picture in the guise of a specific mathematical model. As a result, the methods for implementing a computer representation are significantly dependent on the goals being solved and are occasionally inferior to generalization. As a result, the bulk of these methods is considered non-linear. This affects the need to accumulate the calculation of computer power and the difficulty of algorithms for work acquired through the technical channels of the resulting image. In addition to technical indicators that distort the quality of a digital image, several external moments are considered, and these are: lighting around the scene, moving objects within it, etc. As a result, to obtain the best accuracy of character recognition, it is necessary to take into account all the details. The aim of this work is to study the topic of object recognition in images and video, in order to further use the results of work in creating a system for object recognition in images and video.